Americanization of Karl August Rauschenbusch, 1816-1899 - Schneider, Carl Edward (Church history, 1955)
An interest in August Rauschenbusch may be motivated by the hope that perchance in the life of the father we could discover factors which would illuminate the social-gospel interests of his more famous son. The importance of Rauschenbusch in the early history of German Baptists in North America, particularly as founder and virtual head of the “German Department” of Rochester Theological Seminary for thirty-two years (1858–90), should alone, it could be urged, establish his significance for the religious history of that day. However, it is the primary and less ambitious purpose of this paper to place Rauschenbusch within the framework of the German and American religious situation of the mid-19th century on the basis, largely, of twenty-two of his unpublished letters and a smaller number addressed to him, running from April 12, 1845 to September 27, 1854. These were recently discovered in the archives of the Rhenish Missionary Institute, Wuppertal-Barmen, Germany.